x+26+3x+47-10=x

Simple and best practice solution for x+26+3x+47-10=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+26+3x+47-10=x equation:



x+26+3x+47-10=x
We move all terms to the left:
x+26+3x+47-10-(x)=0
We add all the numbers together, and all the variables
3x+63=0
We move all terms containing x to the left, all other terms to the right
3x=-63
x=-63/3
x=-21

See similar equations:

| 9x+12=-5 | | 22x-30=12x+20 | | -5c+9c-2c-12c-4=6 | | 15/7=25/21-d | | 8t-5=76 | | 12x-28=8x+60 | | 6+5t=4 | | 10x+(-12)=2 | | 5c=1+0 | | 8x+22=46 | | 17x+1=-9 | | 8(9-(9x-8)+9x=0 | | 4x3=120 | | 2(11x-5)=232 | | 8x+22=23 | | 4j-2j+4j=12 | | 10x+(-12)=5 | | 6x+-10=4x+-6 | | 2x+74=4x=68 | | 27+x-3x+47=x | | 3x-3/4=13/6 | | 93=2x+(x+5)+x | | 2(6x^2-5x)=12 | | -8x+4(7x+2)-3(5x-2)=-3x+2(4x+5)+4 | | x2-7=72 | |  3(x−14)=136 | | 27+x-3X=47=x | | 1/4y–3=9 | | -19=47-t | | 7^b=94 | | 49=u+6u | | 9x+5=-25 |

Equations solver categories